Evaluating active mobility: enhancing the framework for social sustainability - Giuseppe Rainieri; Martina Carra; Anna Richiedei; Michele Pezzagno (TeMA: Journal of Land Use, Mobility and Environment)
Active mobility plays a crucial role in reducing traffic congestion, improving air quality, promoting well-being, good health, and fostering social equality, all of which align with the concept of social sustainability within the Sustainable Development Goals (SDGs). However, assessing the impact of active mobility on social sustainability remains challenging due to the lack of clear identification of the specific SDGs influenced by it. This review analyses how previous articles quantify active mobility, its antecedents, and impacts. Additionally, it aims to find if any impacts can contribute to defining Social Sustainability. A Rapid Evident Assessment method was employed in this research in two databases: PsycINFO and Scopus. Out of the first pool of 61 papers, 19 articles were selected. The findings provide a comprehensive framework of the variables that influence active mobility and those influenced by it. Active mobility predominantly contributes to addressing the 11th, 10th and 3rd SDGs. Furthermore, the social sustainability quantification can benefit from assessing active mobility impacts. This work also identifies knowledge gaps, offering valuable guidance for future research in the field.